Taming aggression in your child : how to avoid raising bullies, delinquents, or trouble-makers - Parens, Henri, 1928- (Lanham (Md.) : Jason Aronson, 2012)
Taming Aggression in Your Child: How to Avoid Raising Bullies, Delinquents, or Trouble-Makers is a guide to preventing children from developing aggressive behaviors from birth through adolescence. Hostile destructive kids become hostile destructive adults and often create serious problems for society, and Dr. Henri Parens argues that effective parenting can help prevent aggressive behaviors like bullying, delinquency, and even criminal behavior from developing. Parens explains to caregivers and educators what causes aggression to develop in children and how it affects them as they grow, differentiates between compliance (the goal of effective parenting) and obedience (an often mis-used term, signifying an unquestioning yielding to authority), and explains how to achieve compliance in children through effective limit-setting, discipline, and punishment. He also demonstrates how to help children learn to express hostility in acceptable ways, how to handle temper tantrums in growth-promoting ways, and how to optimize the parent-child relationship in order to minimize the development of aggression in children. Offering concrete strategies for dealing with aggression, Taming Aggression in Your Child is a must read for all parents, whether you are frustrated by your toddler's temper tantrums or worry that your older child is bullying siblings or classmates.
Chapter 1: Can We Tame Human Destructiveness? Chapter 2: What is Aggression? Chapter 3: On Compliance Chapter 4: Achieving Compliance: by Discipline, Limit Setting and Punishment Chapter 5: Helping Children Learn to Express Hostility in Acceptable Ways—and Reduct Teasing, Taunting, and Bullying! Chapter 6: How to Handle Temper Tantrums and Rage Reactions in Growth-Promoting Ways Chapter 7: Optimizing the Parent-Child Relationship
Includes index.
Keywords: Agressie -- Kinderen; Opvoeding; Aggressiveness in children; Aggressiveness in children -- Prevention; Bullying -- Prevention; Child rearing; Parent and child